2008
DOI: 10.1111/j.1365-2567.2008.02828.x
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in the thymocyte phenotype of EphB‐deficient mice largely affect the double negative cell compartment

Abstract: contributed equally to this work. SummaryIn the present study, we have analysed the phenotype of EphB2 and/or EphB3 deficient thymocytes confirming and extending previous studies on the role of this family of molecules in T-cell differentiation. In all mutant thymuses statistically significant reduced cell contents were observed. This reduction of thymic cellularity correlated with increased proportions of apoptotic cells, largely both double negative (DN; CD4 ) CD8 ) ) and double positive (CD4 + CD8 + ) cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
76
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(80 citation statements)
references
References 47 publications
4
76
0
Order By: Relevance
“…However, several data support a direct role of both ephrin-B1 and -B2 expressed by TECs on T cell development. Both ephrin-Bs are expressed by mature TECs (12), and published results reveal that EphB2 and/ or EphB3 forward signaling on thymocytes that depend on signals provided by TECs modulate DP T-TEC adhesion, T cell development, and TCR stimulation (14,45). Therefore, our current results on the effects of TEC-conditioned mutations on adult T cell development can be interpreted as the sum of a direct role plus the indirect consequence of an altered TEC maturation.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…However, several data support a direct role of both ephrin-B1 and -B2 expressed by TECs on T cell development. Both ephrin-Bs are expressed by mature TECs (12), and published results reveal that EphB2 and/ or EphB3 forward signaling on thymocytes that depend on signals provided by TECs modulate DP T-TEC adhesion, T cell development, and TCR stimulation (14,45). Therefore, our current results on the effects of TEC-conditioned mutations on adult T cell development can be interpreted as the sum of a direct role plus the indirect consequence of an altered TEC maturation.…”
Section: Discussionmentioning
confidence: 84%
“…Previous studies have demonstrated a relevant role for some members of this large family of molecules in different aspects of thymus biology. EphB2 and EphB3, and their ligands ephrin-B1 and -B2, are expressed on both thymocytes and TECs (12), and Eph B2 and/or EphB3 knockout mice showed an abnormal thymic development that affects mainly the epithelial component, including the cortex/medulla distribution, TEC morphology, and different epithelial-specific marker expression (13). They also showed decreased numbers of thymocytes and altered T differentiation particularly affecting the DN cell stage (12).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In mammals, there are nine EphAs that bind to five ephrin-As, and five EphBs (B1, B2, B3, B4, B6) that bind to three ephrin-Bs (B1, B2, B3 [2,5,6], their physiological role in immune responses are still not known. Studies have shown that a deficiency of certain Ephs leads to a defect in thymocyte maturation because of abnormal development of the stromal cells [7][8][9][10]. The effects of Eph receptors expressed on mature T cells have been reported, such as modulation of chemotaxis by certain ephrin-As and ephrin-Bs [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…The defects seen in thymocyte maturation in Eph-or ephrin-deficient thymi are thought to result from abnormal development of the stromal cell compartments (27) and modulation of T cell responses (28). For example, EphB2-and/or EphB3-deficient mice exhibit decreased numbers of thymocyte subsets (29), the lack of EphA4 expression results in hypoplastic thymi and decreased numbers of double-positive (CD4 + CD8 + ) thymocytes (27), and blocking fetal thymic organ cultures with EphB2/Fc or ephrin-B1/Fc fusion proteins decreases doublepositive and single-positive T cell populations (30).…”
mentioning
confidence: 99%